THE EFFECT OF INFORMATION SERVICES IN IMPROVING STUDENT UNDERSTANDING ABOUT THE DANGERS OF CYEBRBULLYING CLASS VIII SMPN 24 JAMBI CITY - Syakhroni, Edy (Jurnal Kopendik, 2022)
The purpose of this study is to provide assistance to students through the services provided in counseling guidance such as information services which aim to see how much influence information services have on increasing students' understanding of cyberbullying in order to prevent cyberbullying at SMPN 24 Jambi City. This research is included in a quasi-experimental design research or experiment. sampling technique used simple random sampling technique, which became a population of 200 students of class VIII, then the sample was drawn into 60 students divided into 2 experimental groups and a control group. Based on the treatment that has been carried out on the 2 experimental groups and the control group using different methods, namely the Mind Mapping Method and the question and answer lecture method through information services, it can be seen that the results of the T-test with a Tcount of 2.999 while the Ttable value of 2000 can be concluded that Tcount is greater than Ttable, which means that there is a difference in improvement between the Experiment group and the control group in understanding cyberbullying. Based on these results, the hypothesis says that information services have an effect on increasing students' understanding of cyberbullying Keywords:. Information Services, Cyberbullying, Guidance and Counseling